Malignant melanoma mimicking giant cell variant of glioblastoma multiforme: a case report and review of literature - Arcega, Ramir (Int J Clin Exp Pathol, 2015)
We present a case of metastatic malignant melanoma in a patient initially diagnosed with glioblastoma multiforme, giant cell variant. A forty year old female presented to our institution for a re-resection of a recurrent right parietal lobe mass, presumed to be recurrent glioblastoma multiforme. PET scan during preoperative evaluation revealed a 3 cm left lower lobe lung mass. Metastatic glioblastoma to lung was considered in the differential diagnosis. Resection of the brain mass revealed a highly pleomorphic giant and spindle cell lesion with an immunophenotype strongly supportive of melanoma. Immunostains for melanocytic markers were subsequently performed on the lung biopsy specimen, and demonstrated diffuse staining of the atypical cells, supporting the diagnosis of malignant melanoma in the lung. This case demonstrates the importance of considering melanoma in the differential in any tumor with high grade features.